Grain-filling rate and yield in two rice (Oryza sativa L.) varieties based on critical period of weed control - Lwin, Mar Oo (2014)
Rice (Oryza sativa L.) is the staple food crop for more than half of the world population. Weed density, duration of infestation and crop growth stages are critical factors which affect rice yield potential. Little has being studied on crop physiological responses to weed infestation, especially during reproductive growth stage. Therefore, this study was carried out to evaluate the grain filling rate and effective grain filling period during different times of weed free and weedy periods. The glasshouse experiments following normal rice culture techniques were conducted for two trials at Field-2, Department of Crop Science, Faculty of Agriculture, Universiti Putra Malaysia (UPM). Two rice varieties; MR263 and IR64,were used to determine grain filling rate (GFR) and effective grain filling period (EGFP) during critical period of weed control,. The critical period of weed control was the different between the two varieties. The critical period of weed control for5% yield loss for MR263 and IR64 was observed from 10 to 64 DAS and 5 to 91 DAS for Trial I and 13 to 76 DAS and 7 to 65 DAS for Trial II, respectively. For yield losses of 10% level, the critical period of weed control was observed from 19 to 52 DAS and 18 to 63 DAS for MR263 and 10 to 75 DAS and 12 to 55 DAS for IR64 for Trial I. The highest grain filling rate was observed when rice plants were free of weeds from sowing to harvest, (T5), which was in the range of 0.7 to 0.9 mg/seed/day for both varieties in both seasons. The EGFP for both varieties varied between 27 – 29 days for Trial I and 24 – 27 days for Trial II. Grain filling rate was highly correlated with the final grain yield of MR263 and IR64. However, the effective grain filling period was negatively correlated with the grain yield of both rice varieties. It was found that GFR (mg/seed/day) and EGFP (days) contributed significantly to the final seed weight of both varieties. Percentage filled grain, panicle numbers and final seed weight and grain yield were highly correlated with grain filling rate for both varieties during two trials. EGFP is inconsistent in contributing to the final grain yield of the two varieties used in this study. There were no correlation of effective grain filling duration and grain filling rate with grain yield based upon varieties. Long duration of weed interference during grain filling can reduce grain filling rate,and lead to reduction in final seed weight. Weed free from sowing to harvest (T5) increased the grain filling rate and grain yield for both varieties. Therefore, grain filling rate and yield parameters were affected by weeds interference with crop which contributes to reducing grain yield.